An ethic of mutual respect : the Covenant Chain and aboriginal-crown relations - Morito, Bruce (UBCPress, 2012)
Over the course of a century, until the late 1700s, the British Crown, the Iroquois, and other Aboriginal groups of eastern North America developed an alliance and treaty system that came to be known as the Covenant Chain. In An Ethic of Mutual Respect, Bruce Morito offers a philosophical interrogation of the predominant reading of the historical record, overturning assumptions and demonstrating the relevance of the Covenant Chain to the current First Nations--Crown relationship. By examining the forms of expression contained in colonial documents, the Record of Indian Affairs, and related materials, Morito locates the values and moral commitments that underpinned the parties' strategies for negotiation and reconciliation. What becomes apparent is that these interactions developed an ethic of mutually recognized respect that was coherent and neither culturally nor historically bound. This ethic, Morito argues, remains relevant to current debates over Aboriginal and treaty rights as they pertain to the British Crown tradition. Real change is possible if the focus can be shifted from piecemeal legal and political disputes to the development of an intercultural ethic based on trust, respect, and solidarity.